Escherichia coli thrives in soil 24 months after grazing exclusion in a rainfed Mediterranean biodiverse pasture - Verheijen, Frank; Jelinčić, Antun; Jeffery, Simon; Domingos, Tiago; Khodaparast, Zahra; Bastos, Ana Catarina (Frontiers in Environmental Science, 2025)
Escherichia coli is a facultative anaerobic bacterium mainly found in the lower intestines of mammals. It is transferred to soils via animal feces and can splash onto plant surfaces during rainfall or be taken up through roots into the plant tissue. Subsequently, it can pose a risk to farm workers handling the soil or the vegetation, or groundwater quality through leaching. Many inoculation studies show that E. coli can survive in soils for weeks to months. The few field studies that have been published suggest E. coli can survive for longer in cold and wet soils. We analyzed 20 topsoil samples from a relatively warm and aerobic Mediterranean pasture soil where grazing, and therefore manure inputs, had been excluded for 24 months, using the shotgun DNA sequencing method. We found that E. coli had not only survived for 2 years, but it had also comparatively thrived, as evidenced by its relative abundance of 17.0% in the control treatment and 20.2% in the biochar-amended treatment (no significant difference). Within-treatment variation was low for the control soil (coefficient of variation of 0.15) and approximately double that for the biochar-amended soil (0.28). There were no correlations between the relative abundance of E. coli and soil organic matter content, available P, soil texture, pH, or other soil nutrients. Our results suggest the existence of a naturalized E. coli soil population, with potentially important implications for farm management, as well as for environmental and public health under the One Health umbrella.